Nature-based solutions in peri-urban areas as climate action measures: Case study of the Parelheiros region in the municipality of São Paulo - Pantaleão, Cristiane Criscibene; Cortese, Tatiana Tucunduva Philippi (National Journal of City Management, 2025)
Objective – To present an account of the NBS found in the Parelheiros district, a peri-urban area of ​​the city of São Paulo, describing their potential as strategies for mitigating and adapting to climate change. Methodology – Using a qualitative approach, this research was based on a case study of a peri-urban area as the research strategy. Indirect observation was used, through interviews, bibliographical and documentary research. Content analysis and text analysis supported the assessment and validation of the findings. Originality/relevance – This research sheds light on climate change from a perspective of benefit, hope and promise of opportunities, viewing peri-urban areas as a scenario for transformation at the community scale that expands to the territorial scale and establishes itself at the city scale. Results – The findings showed that NBS stand out for their ability to provide multiple benefits in all spheres of sustainability and in the face of the challenges of climate change. Theoretical/methodological contributions – Territories such as the Parelheiros region, which embrace and strengthen transformation initiatives, can be a reference for other similar areas of the municipality and other cities. Social and environmental contributions – The advantages of these actions can reach all scales of the city, expanding to the state, national and even global levels, promoting the construction of resilience in the face of current and future threats arising from climate change.